Minmasi Waktu Produksi Sepatu Allstar Type Chuck Taylor Low Cut Menggunakan Value Stream Mapping (VSM) dan Penjadwalan - Setyawan, Widy; Maifal, Iwan (Universitas Suryakancana, 2017)
Abstractâ€” CV.Cipendawa is a shoe company, which was established in 2005. The brand of goods produced is Allstar shoes, which become main products. Problems that occur in the process of shoe production Allstar is a waste in the form of idle time (idle time). Waste in the form (idle time) occurs because the company does not pay attention to the existence of alternative Allstar shoe assembly making the engine scheduling less good. This research is done by using lean manufacturing and machine scheduling, in lean manufacturing concept in using the operation of process chart (OPC) and value stream mapping (VSM) to describe the value in production process which includes material and information flow. While the machine scheduling is used to reschedule the production process of Allstar shoes so it is expected to reduce waste. The purpose of this research is to minimize the time of completion of production by paying attention to the assembly alternatives on the production floor. The results of this study indicate that with the scheduling of machines that pay attention to the order of prakitan get the completion time of production of 718 seconds and the waiting time of 114 seconds.dan on making a single shoe score add value of 7102 secondsÂ Keyword : value stream mapping and Scheduling machine.